High-performance ternary nickel-cobalt-manganese oxide nanoparticles-anchored reduced graphene oxide composite as Li-ion battery cathode: Simple preparation and comparative study. Issue 16 (November 2019) - Zhang, Wen; Han, Tianli; Cheng, Mengying; Zhang, Min; Zhong, Yan; Cheng, Dong; Zhou, Ping; Liu, Jinyun
Abstract: Cathode materials of Li-ion batteries are important for their overall Li-storage performance. However, current cathodes are still non-ideal with rapid capacity decay and poor stability. Herein, a composite cathode consisting of ternary LiMn1/3 Co1/3 Ni1/3 O2 particles anchored on reduced graphene oxide sheets is presented, which is prepared through a simple route. The composite cathode exhibits a stable capacity exceeding 120 mAh g −1 after 500 cycles at 0.2 C, along with a high Coulombic efficiency close to 100%, which are obviously improved compared to the pure LiMn1/3 Co1/3 Ni1/3 O2 . In addition, the rate-performance of the composite is also significantly enhanced. We believe that the good electrochemical performance and the general preparation approach are able to enable the composite to find significant applications in high-performance secondary batteries.